Methane and carbon dioxide fluxes from Limonium residues decomposition in saltmarsh soils: effects of tide regime - Elisa Pellegrini; Federico Floreani; Marco Cortin; Maria De Nobili (EQA, 2015)
The flooding regime of saltmarshes strongly affects organic matter mineralisation, representing a unique situation where oxygen diffusion is either impeded by submersion or favoured by retreating water in regular cycles within the same day. Decomposition of Limonium vulgare Mill. residues in saltmarsh soils was evaluated measuring CO2 and CH4 emissions. Four different saltmarshes from the Grado Lagoon (Northern Adriatic Sea) were investigated. Soils were characterised by a similar vegetation (Sarcocornietea class) and similar high coverage of L. vulgare (70-75%) but differed in redox potential, texture and organic carbon content. Hydromorphic conditions were reproduced in mesocosms, and soils were 20 incubated under fully aerobic, fully anaerobic and transient (6 hours cycles) tidal states. Partially decomposed litter (leaves) of L. vulgare was added and 22 decomposition processes were monitored through CO2 and CH4 emissions. Larger CO2 emissions were measured under aerobic conditions, in particular in soil samples with coarse texture. Fully anoxic and tidal regimes showed a similar behaviour. On the contrary, CH4 emissions were less dependent upon flooding, showing only slightly larger values under completely submerged conditions. Larger CH4 emissions have been obtained in fine textured soils. Soil organic matter content also influenced gas emissions: larger values corresponded to higher emissions of both CO2 and CH4.